2017
DOI: 10.1016/j.watres.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation and ecotoxicology of acyclovir in water under UV254 and UV254/H2O2 processes

Abstract: The photochemical and ecotoxicological fate of acyclovir (ACY) through UV direct photolysis and in the presence of hydroxyl radicals (UV/HO process) were investigated in a microcapillary film (MCF) array photoreactor, which provided ultrarapid and accurate photochemical reaction kinetics. The UVC phototransformation of ACY was found to be unaffected by pH in the range from 4.5 to 8.0 and resembled an apparent autocatalytic reaction. The proposed mechanism included the formation of a photochemical intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 53 publications
(12 reference statements)
0
37
0
12
Order By: Relevance
“…Furthermore, subjection to efavirenz (20.6 ng L -1 ) elicited hepatocyte cell damage and even caused death in O. mossambicus ( Robson et al, 2017 ) . Ecotoxicity assay for acyclovir revealed that toxicity on V. fischeri, Raphidocelis subcapitata , D. magna can be reduced upon treatment with UV 254 (1.62 ×10 −3 mol ein −1 )/H 2 O 2 (30-150 mg L -1 ) ( Russo et al, 2017 ) . Emtricitabine and Nevirapine are reported by Ngumba et al (2016), to show toxicity for water flea, algae and fish.…”
Section: Antiviral Drugs: Environmental Occurrence and Potential Ecotmentioning
confidence: 99%
“…Furthermore, subjection to efavirenz (20.6 ng L -1 ) elicited hepatocyte cell damage and even caused death in O. mossambicus ( Robson et al, 2017 ) . Ecotoxicity assay for acyclovir revealed that toxicity on V. fischeri, Raphidocelis subcapitata , D. magna can be reduced upon treatment with UV 254 (1.62 ×10 −3 mol ein −1 )/H 2 O 2 (30-150 mg L -1 ) ( Russo et al, 2017 ) . Emtricitabine and Nevirapine are reported by Ngumba et al (2016), to show toxicity for water flea, algae and fish.…”
Section: Antiviral Drugs: Environmental Occurrence and Potential Ecotmentioning
confidence: 99%
“…7 Accordingly, some alternative approaches have already been explored for the removal or degradation of NSAIDs, 8 as well as adsorption, electrochemical oxidation, photo-degradation, ultrasonic irradiation, and advanced oxidation process. [9][10][11][12][13][14][15][16][17] However, adsorption has been found to be the most appropriate technology due to its low-cost, exactitude, feasibility, the simplicity, and safety of the treatment process. [18][19][20][21][22][23][24][25] Moreover, a number of adsorbents such as functionalized carbon nanotubes (FCN), graphene, polystyrene-divinylbenzene resin, activated carbon, and etc.…”
Section: Introductionmentioning
confidence: 99%
“…This could consequently entail more adverse effects to human health than other classes of drugs (Jain et al, 2013). Moreover, further drawbacks are represented by AVs low biodegradability and their increasing use during pandemic outbreaks (Funke et al, 2016;Hill et al, 2014;Russo et al, 2017).…”
Section: Potential Environmental Impact Of Administered Drugsmentioning
confidence: 99%